AUTOMATED SENSORY MONITORING SYSTEM PROTOTYPE FOR CONTINUOUS MONITORING OF MATERIAL AND STRUCTURE STATE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The goal of this article is to solve problems of automated monitoring systems of industrial and aviation constructions. Based on the latest research results, the most cost-effective solutions are covered, and a practical solution is offered. This article is part of the scientific project “Development of an integrated sensor system for material and structure monitoring”. The article describes the problem and suggests a practical solution for an integrated sensor system for material and structure monitoring prototype.